Spin Bias in randomized controlled trials of botulinum toxin for bruxism management: a meta-epidemiologic study - Graziela De Luca Canto; Patrícia Pauletto; Cristine Miron Stefani; Thais Marques Simek Vega Gonçalves; Nelson Carvas Junior; Carlos Flores-Mir; Ana Carolina Pereira Nunes Pinto; Virginia Fernandes Moça Trevisani (BMC Medical Research Methodology)
Abstract Objective To perform a quantitative and qualitative analysis of spin bias in randomized clinical trials (RCTs) focusing on botulinum toxin (BTX-A) for managing bruxism. Study design and protocol This is a meta-epidemiologic study. The protocol was registered on the Open Science Framework. Study selection We included RCTs that evaluated the effectiveness of BTX-A for managing bruxism, associated or not with signs and symptoms of temporomandibular disorders. The outcomes were changes in pain and bruxism events. Spin bias was investigated in abstract and main text. The frequency of spin bias was assessed, and a qualitative analysis was conducted. The study was classified as effective if the outcome analyzed was statistically significant (p-value 0.05) and reached the minimum important difference of 20% and ineffective if the reported outcome was statistically nonsignificant or the study did not report the p-value or the results did not reach the minimum important difference of 20%. Results An overall frequency of 59.4% spin bias was identified in eight included RCTs. The conclusion in the main text (87.5%) was the section with the highest frequency of spin bias. In the qualitative analysis, the most common strategies identified were inadequate extrapolation to a large population (30.61%), inadequate implication for clinical practice (20.41%), and misleading reporting (12.25%). Conclusion There is a high frequency of spin bias in RCTs that evaluated BTX-A for bruxism management. Close to 90% of the selected RCTs presented spin bias in the main text’s conclusion. The most common spin was the inadequate extrapolation of the results. Clinical Significance Applying BTX into the temporalis did not reduce muscle activity and the results for masseter injections remain controversial. It seems that BTX-A injections can reduce pain from two weeks to one year. It is not possible to have certainty about the efficacy and safety of using BTX-A to reduce pain and bruxism events.